MEASURING LEARNING STYLES AND LEARNING STIMULUS AMONG SECONDARY SCHOOL STUDENTS - Sultana, A; Muthurajan, P; Khairuddin, Amira (PEOPLE: International Journal of Social Sciences, 2017)
This study examines learning styles and learning stimulus among secondary school students in Malaysia. A total of 50 students from Sekolah Menengah Kebangsaan Ungku Aziz, Sabak Bernam in Selangor were interviewed to measure student’s different styles. The adapted version of Dunn and Dunn Learning Styles Inventory were used as in this study. The findings showed that majority students preferred on grouping learning styles (M=4.07), visual learning styles (M= 3.88), auditory learning styles (M=3.66), individual learning styles (M=3.61) and kinesthetic learning styles (M= 4.07) respectively. Based on the findings, several suggestions have been made to enhance the academic achievement for students. The results of this study provide useful information for teachers and students which are important for the process of learning.